pH-responsive polymersome-mediated delivery of doxorubicin into tumor sites enhances the therapeutic efficacy and reduces cardiotoxic effects - Albuquerque, Lindomar J C; Sincari, Vladimir; Jäger, Alessandro; Kucka, Jan; Humajova, Jana; Pankrac, Jan; Paral, Petr; Heizer, Tomas; Janouškova, Olga; Davidovich, Irina; Talmon, Yeshayahu; Pouckova, Pavla; et al. (Journal of controlled release, 2021)
The delivery of therapeutics into sites of action by using cargo-delivery platforms potentially minimizes their premature degradation and fast clearance from the bloodstream. Additionally, drug-loaded stimuli-responsive supramolecular assemblies can be produced to respond to the inherent features of tumor microenvironments, such as extracellular acidosis. We report in this framework the use of pH-responsive polymersomes (PSs) manufactured using poly([N-(2-hydroxypropyl)] methacrylamide)35-b-poly[2-(diisopropylamino)ethyl methacrylate]75 as the building unit (PHPMA35-b-PDPA75). The self-assemblies were produced with desired size towards long circulation time and tumor accumulation (hydrodynamic diameter - DH ~ 100 nm), and they could be successfully loaded with 10% w/w DOX (doxorubicin), while maintaining colloidal stability. The DOX loaded amount is presumably mainly burst-released at the acidic microenvironment of tumors thanks to the pH-switchable property of PDPA (pKa ~ 6.8), while reduced drug leakage has been monitored in pH 7.4. Compared to the administration of free DOX, the drug-loaded supramolecular structures greatly enhanced the therapeutic efficacy with effective growth inhibition of EL4 lymphoma tumor model and 100% survival rate in female C57BL/6 black mice over 40 days. The approach also led to reduced cardiotoxic effect. These features highlight the potential application of such nanotechnology-based treatment in a variety of cancer therapies where low local pH is commonly found, and emphasize PHPMA-based nanomedicines as an alternative to PEGylated formulations.
Keywords: Drug Carriers; Nanomedicine; doxorubicin; Female; Doxorubicin; Drug Delivery Systems; zvířata; myši; myši inbrední C57BL; Mice; ženské pohlaví; pH-responsive polymersomes; lékové transportní systémy; Mice, Inbred C57BL; Hydrogen-Ion Concentration; Neoplasms; nosiče léků; Tumor Microenvironment; nádory; nádorové mikroprostředí; Antitumor activity; kardiotoxicita; Animals; koncentrace vodíkových iontů; Cardiotoxicity